Physical Education Motor Skills Test in Primary School in the Last 5 Years: A Systematic Review - Arif Al Ardha, Muchamad; Sawa Bikalawan, Sauqi; Nurhasan, Nurhasan; Edhu Wigraha, Sheva; Mark Arbaan, Jay; Chung Bing Yang (Proceeding of International Joint Conference on UNESA, 2025)
The development of a child’s movement is an essential period or phase in their growth and development. Movement development becomes an important foundation for a child in gaining good movement effectiveness in the future. This study aims to systematically review some literature that has developed or tested instruments related to movement skills in elementary school students in the last five years. This study is a systematic review study by adopting the Preferred Reported Item for Systematic Reviews and Meta-Analyses (PRISMA) method in conducting data collection. The researcher used single database as the database of this systematic review research. The data collection process using the PRISMA method integrated with the SCOPUS website, obtained initial identification results of 929 documents. Furthermore, the results of articles that fit the inclusion criteria were 210 articles. The results were sorted and selected again until finally obtaining 10 articles with the most citations. These findings highlight the necessity for a more adaptable methodology in the future development of fundamental movement assessment tools. The proposed instruments should fulfill validity and reliability criteria while also addressing practical considerations, including ease of administration, adaptation to diverse facility settings, and alignment with the requirements of educators in the field.